2020
DOI: 10.1037/adb0000533
|View full text |Cite
|
Sign up to set email alerts
|

Examining the ecological validity of the prototype willingness model for adolescent and young adult alcohol use.

Abstract: The present study is the first ecologically valid, daily level test of the prototype willingness model (PWM), a model previously tested with hypothetical scenarios to investigate the social reaction and reasoned pathways toward engaging in health-risk behavior. The purpose of the present study is to examine whether days with elevated alcohol-favorable PWM cognitions are also associated with greater intentions and willingness to drink and increased drinking behavior on that day. Participants included 15–25-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…In addition to corroborating evidence that intentions and willingness vary by occasion, we also demonstrate that intentions and willingness are perceived to shift within the drinking event, which calls into question the current practice of assessing these constructs once daily. We recommend that future work include assessments of intentions and willingness more proximal to the drinking event (e.g., afternoon vs. morning assessment; Lewis et al, 2020) and, if possible, include repeated assessments of these constructs during the drinking event itself.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to corroborating evidence that intentions and willingness vary by occasion, we also demonstrate that intentions and willingness are perceived to shift within the drinking event, which calls into question the current practice of assessing these constructs once daily. We recommend that future work include assessments of intentions and willingness more proximal to the drinking event (e.g., afternoon vs. morning assessment; Lewis et al, 2020) and, if possible, include repeated assessments of these constructs during the drinking event itself.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that peoples' daily or momentary coping and enhancement motives for drinking are robust predictors of same day emotional drinking (Stevenson et al, 2019;Votaw & Witkiewitz, 2021). Other cognitive factors, such as cravings (Serre et al, 2015;Waddell et al, 2021), the momentary reinforcement value of alcohol (Murphy & Mackillop, 2006), and other drinking-related cognitions (Lewis et al, 2020) have been shown to vary within person and may be important for understanding how drinking motives are enacted to influence alcohol use in daily and momentary data.…”
Section: Implications For Motivational Models Of Alcohol Usementioning
confidence: 99%
“…Despite strong empirical support that willingness prospectively predicts real-world use, future studies incorporating real-time assessments of use and competing mechanisms (e.g., expectancies, motives, intentions, and craving) across methods (e.g., laboratory-based; EMA) are needed (Anderson et al, 2013, 2014; Lewis et al, 2019). Another concern is whether this study was statistically powered to detect the moderation of SA and Rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol and cannabis are the two most widely used substances in the U.S. with initial rates of use and use-related disorders peaking in emerging adulthood (Franco et al, 2019; Grant et al, 2015; Hasin et al, 2016; Schulenberg et al, 2019). Emerging adults (18–25 years) in college are at particularly high risk for substance use, in part, because college campuses provide more opportunities to use substances in higher-risk contexts (e.g., at parties with people they do not know well) and regularly engage with substance-using peers (Allen et al, 2017; Arnett, 2005; Lewis et al, 2019). Socially anxious individuals who are hypersensitive to social cues and the fear of potential rejection may be at an even greater risk for developing use-related problems during this time (Abrams et al, 2001; Buckner et al, 2012; Conway et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation